Extendable Dining Table Inspired by Air Hockey Table for Open Concept House - Jun Hao, Too; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2021)
A dining table is a central element for houses where house members or family gather, especially for meals. A standard or traditional dining table has a fixed number of users, which might be sufficient to accommodate all family members staying together in one house. An issue arises when more people visit or come for a special occasion such as a birthday party, gatherings, dinner party, and many more. A fixed number of seats will cause difficulty to provide seating for all at once. People need to wait for their turn to enjoy their food or use furniture such as a foldable table or sit on the floor. This situation makes the house owner awkward as they need to serve their guests as best as possible. Therefore, this study aims to design an extendable dining table with a capacity range from 4 to 8 persons inspired by the air hockey table. In this study, the questionnaire was distributed online via Google Form. The design and manufacturing process is influenced by the data obtained from the questionnaire. Design criteria in designing an extendable dining table include a modern concept that suitable to accommodate 4 seats (normal setting) to 8 seats (extended), using wood as a material with a butterfly leaf extendable concept of the top table. The attractive modern extendable dining table inspired by the air hockey table fabricated in this study meets the consumers' requirements based on the input gained from the questionnaire. This will bring added value and potential commercial value for commercialization.